Farmer's Capacity of Palm Integrated Beef Cattle Businesses on Manokwari District, Indonesia - Anwarudin, Oeng; Herawati, Maria; Isty, Gallusia Marhaeny Nur (Agro Bali : Agricultural Journal, 2025)
The research aims to analyze the capacity of farmers and the factors that influence the capacity of farmers in the integrated palm oil beef cattle business in Manokwari Regency. The research was carried out in Manokwari Regency, West Papua. The sample was 228 breeders using the proportional cluster random sampling technique. Primary data was collected using questionnaires, in-depth interviews, and FGD. Independent variables consist of individual characteristics, support from external factors, and the role of agricultural instructors. The dependent variable of this research is farmer capacity. Analysis techniques used descriptive statistics and SEM (Structural Equation Models). The results show that the business capacity of farmers in the palm oil integrated beef cattle business is in the low category, which is indicated by the ability of farmers who do not pay attention to the technicalities of integrated cattle cultivation, such as the majority of cattle breeds whose mothers and bulls are unknown, raising livestock in oil palm plantations with lack of supervision, the mating system naturally, with any male, no health checks and deworming are ever carried out, easy marketing conditions mean that efforts to establish cooperation are not a concern. The capacity of farmers in the integrated beef cattle business on oil palm plantations is directly influenced by (1) the individual characteristics of the farmer as reflected by formal education, number of livestock, perception and motivation of the farmer; (2) External support reflected by government, family, institutional and market support; (3) the role of agricultural instructors as facilitators, communicators and consultants.